P31 Review of home mechanical ventilation in patients living with motor neurone disease. (12th November 2019) - Rajan, KK; Sheridan, S; Murphy, P; Suh, ES; Marino, P; Pattani, H; Steier, J; Hart, N; Kaltsakas, G; Ramsay, M
Abstract : Introduction: Home mechanical ventilation (HMV) improves quality of life and survival in MND patients (Bourke et al, 2006). We report the clinical data of MND cohort managed in a complex home ventilation centre. Methods: Medical records of 84 patients, referred from 1st of January 2017 to 1st of January 2018, were retrospectively reviewed and followed up to 1st January 2019. Chronic respiratory failure was defined as an arterial partial pressure of carbon dioxide or transcutaneous carbon dioxide value greater than 6kPa. Difference in ventilation settings were calculated using a paired t-test or McNemar's test for proportions. Rate ratio reduction in mortality was calculated using the Mantel–Haenszel-type method. Results: The mean age of the cohort was 68±9.1 years and 54 patients (52%) were male. Twenty-seven patients (32%) had bulbar onset, 46 (55%) limb onset, 5 (6%) mixed onset and 6 (7%) unknown, having died before review. Forty-eight patients (57%) died, 34 (40%) survived during the observation period and 2 (2%) declined to be seen. Survival time for all patients was 334 days (IQR 144–453) from referral date. Median number of visits was 3 (1–6). At first visit, 29 patients (43%) demonstrated chronic respiratory failure. Forty-two patients (52%) received outpatient HMV treatment at first review with a further 22 (26%) initiated during the observation period. Ventilators settings at initiation and final review are shown in Table 1. Of patients initiated on HMV 38% never used it and the daily HMV usage of users was 9.3 hours (5.5–18.8). 50% of patients used HMV for >4 hours and had higher survival from the referral date (437 days, 341–549) compared to patients using <4 hours (242 days, 135–437). Additionally, they had a risk reduction in mortality compared to patients using <4 hours (0.37 95% CI 0.19–0.74 p=0.003). Conclusion: This retrospective review suggests that HMV increases survival in MND patients if they are able to tolerate and adhere to the treatment for >4 hours. Using HMV even for short periods may confer a survival benefit. A streamlined pathway with dedicated respiratory MND team is required to manage these patients in an effective and timely manner.